Reef related fisheries resources, spawning and nursery grounds of target species in Quy Nhon bay, Binh Dinh province - Long, Nguyen Van; Mai, Xuan Dat; Thai, Minh Quang (Vietnam Journal of Marine Science and Technology, 2021)
Coral reef-related fishery resources in Quy Nhon bay were assessed at four communes in 2016, using an investigation note with additional input from consultations with experienced local fishermen. This information was ground-truthed during field survey assessments of spawning and nursery grounds of target resources (December 2016 and April–June 2017). The total catch of reef-related target resources was about 637 tons/year, including 536 tons of fish, 130 tons of mollusks, 0.34 tons of spiny lobsters, 19 tons of collector urchins, and 3 tons/year of Gracilaria seaweeds. There were some 936,450 juveniles of fishes and lobster caught in each year, in which some 576,000 individuals of grouper juveniles (orange-spotted grouper and six-bar grouper) were mainly caught by Ghenh Rang commune, and some 360,450 individuals of lobster ‘seeds’ were caught by the four communes (Nhon Ly, Nhon Hai, Ghenh Rang and Nhon Chau). The total revenue from fishing at the 4 locations was some 90.81 billion VND (about 4,128,000 USD), with the highest value being recorded in Nhon Hai (41.23 billion VND), Nhon Ly (28.53 billion VND), Ghenh Rang (13.06 billion VND), and the lowest in Nhon Chau (7.99 billion VND). Commercial resources contributed 35.43% (32.17 billion VND) and seed collection 64.57% (58.64 billion VND). There were 16 important grounds found in Quy Nhon bay, including three spawning grounds of cuttlefishes and murex snails, and 13 nursery grounds of swimming crabs, lobster ‘seeds’, sea cucumbers, rabbitfishes, and groupers, in which Nhon Hai and Ghenh Rang supported six grounds for each.